Introduction to solid modeling using SolidWorks 2010 - Howard, William E. [ (William Edward)] , 1957-; Musto, Joseph C. (McGraw Hill, 2011)
The text Introduction to Solid Modeling Using SolidWorks[registered] 2010 presents solid modeling not just as a communication tool, but as an essential part of the design process. To this end, the text explores design intent, the use of solid models in engineering analysis, and introduces techniques from manufacturing such as mold design and sheet metal patterning. Howard and Musto provide a student-friendly presentation filled with easy-to-use tutorials. Their approach is also designed to help students understand how engineering is used in the real world. For instance, modeling exercises are largely centered on examples drawn from industrial applications. SolidWorks software is now available to students, so students can apply exactly what they are reading! Introduction to Solid Modeling Using SolidWorks[registered] 2010 presents 'keystroke-level' tutorials, providing users new to the SolidWorks[registered] program with all the detail they need to become confident using the software. Topics are illustrated and infused with examples from the real world such as flanges, brackets, helical springs, and more. Additionally, this easy-to-use guide has modular chapters allowing for flexible organization of a course or self-study